2012
DOI: 10.1186/1471-230x-12-166
|View full text |Cite
|
Sign up to set email alerts
|

IgG and IgG4 antibodies in subjects with irritable bowel syndrome: a case control study in the general population

Abstract: BackgroundPatients with Irritable Bowel Syndrome (IBS) often relate their symptoms to the intake of food and modify their diet. IgE-mediated food allergy is uncommon in IBS, but the role of IgG-mediated food hypersensitivity remains inconclusive. The primary aim of this study was to compare food- and yeast-specific IgG and IgG4 antibodies in subjects with and without IBS.MethodsThis was a case control study in the general population for which subjects completed questionnaires about abdominal complaints and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
0
38
0
4
Order By: Relevance
“…16,17 Like atopic conditions, those observations suggest the possibility of a role of IgG4-related immune reaction in the pathophysiology of IBS. In a study from the United Kingdom, IBS patients had significantly higher IgG4 titers to wheat, beef, pork, and lamb compared to controls.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…16,17 Like atopic conditions, those observations suggest the possibility of a role of IgG4-related immune reaction in the pathophysiology of IBS. In a study from the United Kingdom, IBS patients had significantly higher IgG4 titers to wheat, beef, pork, and lamb compared to controls.…”
Section: Discussionmentioning
confidence: 84%
“…In a study from the United Kingdom, IBS patients had significantly higher IgG4 titers to wheat, beef, pork, and lamb compared to controls. 16 In contrast, a study from China showed that IBS patients had significantly higher levels of IgG antibody to crab, egg, shrimp, soybean, and wheat than controls. 17 In that study, patients with functional dyspepsia also had significantly higher titers of IgG antibody to egg and soybean, compared with controls.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bunlardan en önemlisi; bireylerde aşırı duyarlılık gösteren besinlerin belirlenmesinde immünglo-bulin (IgG) veya IgE testleriyle ilgili tutarsızlıklar olduğudur. 23,24 Ligaarden ve ark., sağlıklı ve İBS tanısı alan hastalarda IgG testi pozitif olan besinlerin oranının benzer ve IgG testinin İBS tedavisinde kullanımının kısıtlı olduğu sonucuna varmışlardır. 23 Başka bir çalışmada ise IgG pozitif olan besinlerin kısıtlanmasıyla kontrol grubuna göre %10 daha iyi fayda sağlandığı görülmüştür.…”
Section: İrri̇tabl Barsak Sendromu Ve Di̇yet İli̇şki̇si̇unclassified
“…23,24 Ligaarden ve ark., sağlıklı ve İBS tanısı alan hastalarda IgG testi pozitif olan besinlerin oranının benzer ve IgG testinin İBS tedavisinde kullanımının kısıtlı olduğu sonucuna varmışlardır. 23 Başka bir çalışmada ise IgG pozitif olan besinlerin kısıtlanmasıyla kontrol grubuna göre %10 daha iyi fayda sağlandığı görülmüştür. 24 İBS'de besin allerjisi varlığı ve İBS semptomlarında besin intoleransının da rol oynayacağına dair kesin bir kanıt mevcut değildir.…”
Section: İrri̇tabl Barsak Sendromu Ve Di̇yet İli̇şki̇si̇unclassified